Perception of First-Year Medical Students Towards Cadaveric Oath - Singh, Poonam; Phuyal, Naveen; Khadka, Sulochana; Thapa, Trilok Pati; Thakur, Sujit Kumar (Journal of Nepal Health Research Council, 2023)
Background: Cadaveric oath-taking is a special way of expressing respect and gratitude to the donors and their families of medical students. The cadaveric oath-taking ceremony was organized for the first time in our medical college. Our study was carried out with the aim of understanding the perceptions of the students after the oath-taking ceremony. Methods: This is a descriptive cross-sectional study conducted in the Department of Anatomy among first-year medical students of a medical college. The total sample size was 100. Data was collected using a pre-structured questionnaire among a group of students who took part in a cadaveric oath-taking ceremony, conducted for the first time in the medical college. Results: Sixty-eight percent of the respondents strongly agreed that cadaveric oath is important in anatomy learning. Eighty-four percent of respondents fully agree with the fact that cadavers are silent mentors. About 88.00% of respondents strongly agreed that they should be thankful to the family members for the noble gesture of body donation. Ninety-five percent of respondents strongly feel that cadavers should be treated with respect, compassion, care, and dignity. Conclusions: The cadaveric oath-taking ceremony holds significant importance in medical education, providing a unique opportunity and avenue to pay tribute to donors and acknowledge their generous contributions. Our study strongly supports integrating the cadaveric oath ceremony at the start of anatomy dissection, fostering ethical principles among aspiring doctors, and honoring the invisible guides in the field of medical education. Keywords: Anatomy; cadavers; cadaveric oath